The impact of pleasantness ratings on crossmodal associations between food samples and musical notes - Crisinel, A; Spence, C (2012)
Although several crossmodal associations involving taste and olfaction have been reported recently, the mechanism(s) by which they operate are still poorly understood. In the present study, we explored the role of a single parameter that has been suggested to play an important role in taste/flavour-musical note association, namely pleasantness. Chocolate was chosen as a stimulus as it elicits a wide range of pleasantness ratings (especially in the case of dark chocolate). Participants tasted three types of chocolate (dark, milk, and marzipan-filled) and had to match their flavour with a musical note (choosing both the pitch and the instrument playing the note). The results demonstrated that, while there was an overall correlation between pleasantness ratings and the chosen pitch, it disappeared when a single stimulus was considered in isolation, suggesting that pleasantness is not solely responsible for the associations between tastes/flavours and pitch. By contrast, pleasantness affects the choice of instrument even when a single stimulus is considered. The role of pleasantness in driving associations between tastes/flavours and musical notes, while important in the choice of instrument, is thus not as essential for the choice of pitch as has been suggested previously. © 2011 Elsevier Ltd.